Sensibilidad y poder de discriminación de pruebas pedagógicas de ejecución máxima - Cárdenas Ayala, Edgar Aníbal (2023)
In the present research work of a correlational descriptive type, the variables sensitivity and power of discrimination of the items of the pedagogical tests of execution maximum that are applied to the students of the educational institutions of the Junín Region were studied.  The general objective was to statistically analyze and interpret the relationship between the aforementioned variables.  And, as a hypothesis: there is a causal relationship between the psychometric statisticians of sensitivity and the power of discrimination, of the items of the pedagogical tests of execution maximum that are applied to the students of the educational institutions of the Junín Region.  Arriving at the conclusion, among others, that there is a correlation r = 0,951, high, direct with average significance of 0,01 as well, the determination coefficient highlights that up to 91% of the value of sensitivity is determined by the value of the power of discrimination, and 9% is due to other factors; and, that there is equality between the degree of dependence and the degree of influence of sensitivity on discriminative power and vice versa, of the pedagogical tests of execution maximum  that are applied to the students of the educational institutions of the Junín Region.